The Environmental Impacts of Tourism at the Casela Nature and Leisure Park, Mauritius - Ramkissoon, Haywantee; Durbarry, R. (Common Ground Publishing, 2009)
The purpose of this study is to analyze the environmental impacts resulting from tourist activities at the Casela Nature and Leisure Park, an important tourist attraction in the island of Mauritius. The study adopts a qualitative approach to understand the environmental impacts resulting from the behaviour of visitors. In general, the results reveal that tourism is having some positive impacts on the park such as the preservation of many rare plants and animals. Visitor activities however, are also having negative consequences on the environment of the park. During weekends and during morning times, the carrying capacity of the park seems to be exceeded. Noise pollution and litter were some of the most severe impacts resulting from tourist activities. Overcrowding was also another impact noted by the manager of the park which was confirmed by the observation of the authors. The noise pollution caused by activities of the tourists was found to be disturbing to the environment of the park and to animals nearby. Based on the findings, the authors have recommended the implementation of certain visitor management strategies such as displaying a code of conduct for visitors, managing visitor flows and having trained guides for visiting purposes.